Preparing and Improving the Properties of Sodium Acrylate Polymer by Adding Dentonite for the Treatment of Desertification Phenomenon - Hamid A. F. Al-Falahi; Estabraq Ali Hameed (Al-Kitab Journal for Pure Sciences, 2023)
ABSTRACT The phenomenon of desertification has a negative impact on the national economy of any country and may usually be obtained for many reasons such as the removal of agricultural land, depletion of soil, overgrazing, methods of poor irrigation, high temperature, and the lack of rainfall. The following paper tackles solving the problem of the lack of rainfall through the use of chemical methods such as preparing sodium polyacrylate and improving its properties by means of adding bentonite and thus obtaining a new and improved water absorption compound. The study concludes that the suitable range of bentonite ratio that is between (0 - 20 wt %) ensures water absorption from 1340 gg - 1 to 1500gg – 1 and thus the researcher confirms that the cross-linked of the compound will not be changed and the absorption of water will be higher. The presence of bentonite with polymer at a perfect percentage contributes to the reorganization of the distribution of the granular size of the polymer sodium polyacrylate—a matter that is reflected on the growing of its ability to absorb water and thus becoming a suitable compound in the treatment of desertification.